The current status of the Northern white rhino in Garamba - Smith, Hillman (Pachyderm)
Although focused on rhino changes in elephant numbers and poaching pressure are noted. Between 1983 and 1995 the elephant population increased with estimated number in the latter year suggested to be 11117+/-3660. A 1997 aerial survey in the southern sector of the Park, which serves as the main rhino and elephant habitat noted significant poaching activity. A March/April survey in the same area suggested much less poaching activity. Observations recorded 29 fresh and 1 old elephant carcass in June 1997, and 1 fresh and 101 old carcasses. The 1995 population estimate for Garamba was 11175 elephants with 3679 in the southeastern part of the Park, the 1998 estimate was 5487 with 1339 being in the southeastern portion.